REVIEW ARTIKEL : TEKNOLOGI DALAM PENGELOLAAN GUDANG INDUSTRI FARMASI - Isnani, Nazhipah; Malahayati, Siti; Junjung Buih, Putri Helena (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Application of technology in pharmaceutical industry warehouse management, focusing on warehouse management systems such as Warehouse Management System (WMS), Radio-frequency Identification (RFID), and Reorder Point (RO). This study shows that WMS facilitates real-time stock management and storage arrangements, although it requires significant investment. RFID improves product identification efficiency, but is susceptible to frequency interference. Reorder Point systems help in inventory control, but rely on the accuracy of historical data. In addition, artificial intelligence (AI) has the potential to improve operational efficiency, although it requires high-quality data and large investments. The application of these technologies is expected to improve the effectiveness of pharmaceutical warehouse management, ensure product quality and safety, and optimize inventory management. The latest trends such as Agile, Supply Chain 4.0, and Digital Twin are also discussed as methods that are increasingly popular in industry practice. This study is expected to contribute to the development of science and practice in the pharmaceutical field.